The Development of ‘CABASA’ Application as History Learning Media Based Cultural Heritage - Dwi Kurniasih, Atik; Sunardi, Sunardi; Sariyatun, Sariyatun (Pelopor Publikasi Akademika, 2024)
Historical awareness related to Indonesia is mandatory for all Indonesians, namely awareness that we started from the same historical journey of the nation. This research aims to develop the 'CABASA' application as Sragen cultural heritage-based historical learning media is capable of displaying descriptions, as well as photos of cultural heritage. This Development uses three main steps adopted by Borg and Gall: the preliminary stage, the planning stage, and the testing stage. The trial results of the 'CABASA' product developed are suitable for use in the history learning process. The conclusion is the development method adopted in this research is simplified into three main steps. Preliminary development studies and the final stage are product trials. With the product trial results being very feasible, it can be concluded that 'CABASA' can be used as an interactive learning media based on cultural heritage in the Sragen district, which is following current developments where this learning media is straightforward to use.